Determination of the myocardial performance index in deteriorating grades of intrauterine growth restriction and its link to adverse outcomes. (29th December 2014) - Bhorat, I. E.; Bagratee, J. S.; Pillay, M.; Reddy, T.
Abstract Aim The aim of this study is to determine the fetal modified myocardial performance index (Mod‐MPI) and E‐wave/A‐wave peak velocities (E/A ratio) in deteriorating grades of intrauterine growth restriction (IUGR) and its link to adverse outcomes defined as perinatal death, hypoxic ischemic encephalopathy, neonatal resuscitation, neonatal cord pH <7.15, intraventricular hemorrhage and bronchopulmonary dysplasia. Method Forty three pregnant women with IUGR defined as the abdominal circumference <10th percentile for gestational age and umbilical resistance index >2 standard deviations in the third trimester of pregnancy were matched for gestational age and maternal age with 43 women with appropriate‐for‐gestational‐age fetuses. The IUGR group was subdivided on the basis of multivessel Doppler anomalies into different grades of growth restriction. Mod‐MPI and E/A ratio were determined and linked to perinatal outcome. Results The median Mod‐MPI was significantly higher in growth‐restricted fetuses compared with controls (0.59 vs 0.37, p < 0.001) and increased with severity of IUGR, the classification of which was based on degree of abnormality of the umbilical resistance index, presence of arterial redistribution and degree of abnormality of the ductus venosus (DV) Doppler indices. A cut‐off Mod‐MPI value of 0.54 conferred a sensitivity of 87% [confidence interval (CI): 66–97%], specificity of 75% (CI: 55–91%) and a likelihood ratio (LR) of 3.47 for an adverse outcome. A cut‐off Mod‐MPI value of 0.67 conferred a sensitivity of 100% (CI: 54–100%), specificity of 81% (CI: 65–92%) and LR of 5.28 for perinatal death. No abnormal outcomes occurred in controls. In logistic regression analysis, the MPI remained a significant predictor of adverse outcome after adjusting for gestational age of delivery, fetal weight, E/A ratio, maternal age, DV Doppler indices, amniotic fluid index and umbilical artery resistance index [adjusted odds ratio, 95% CI: 2.60 (1.15–5.83), p‐value 0.02]. MPI fared significantly better than the E/A ratio as a predictor of adverse outcome (area under the receiver operating characteristic curve of 0.94 and 0.76, p < 0.001). Conclusion Fetal myocardial performance deteriorates with severity of growth restriction. There is an association between severity of the MPI elevation and rates of adverse perinatal outcome. The Mod‐MPI and E/A ratio have the potential to be integrated into routine surveillance techniques of the growth‐restricted fetus. © 2014 John Wiley & Sons, Ltd.